Collective escape waves provide a generic defence against different avian predators - David Bierbach; Juliane Lukas; Luis Gómez-Nava; Fritz A. Francisco; Lenin Arias-Rodriguez; Stefan Krause; Korbinian Pacher; Yunus Sevinchan; Pawel Romanczuk; Jens Krause (Royal Society Open Science)
In many animal species, collective behaviours can be explained by a simple set of interaction rules. It is an intriguing question whether this generality at the level of mechanism also translates into generality at the level of function. Assuming that collective behaviour provides antipredator benefits for the partaking individuals, we ask whether the same collective behaviour provides protection against different predators in general. We investigated this question in sulphur-adapted fishes in their natural habitats in Mexico. Here, fish schools are frequently attacked by many different bird species and fish respond with synchronized and often repeated collective diving behaviour (escape waves). We found all bird species to wait longer until they attacked as they encountered more waves, both before they launched their first attack (pre-attack) and between subsequent attacks (post-attack). Post-attack, all bird species triggered similarly high numbers of waves while species differed in the number and the interval between the waves they triggered pre-attack. Through simulated bird arrivals, we confirmed that birds in the pre-attack context could be perceived as less threatening or completely overlooked, depending on their size, colouration and contrast to the background. We argue that the generality in the fish’s collective response as well as the similarity in effect on the different birds’ hunting behaviour might be explained by waves targeting a weakness in the visual processing ability common to different predators.